Sulfasalazine induces autophagy inhibiting neointimal hyperplasia following carotid artery injuries in mice - Zhang, Weichang; Yan, Cheng; Xiao, Yangyan; Sun, Yuxin; Lin, Youjun; Li, Qinglong; Cai, Wenwu (Frontiers in Bioengineering and Biotechnology, 2023)
Background: Neointimal hyperplasia (NH) is a crucial pathophysiological feature in vascular transplant and in-stent restenosis. Excessive proliferation and migration of vascular smooth muscle cells (VSMCs) play important roles in NH. This study aims to explore the potentialities and mechanism of sulfasalazine (SSZ) in the prevention of restenosis. Methods: Sulfasalazine was encapsulated in nanoparticles made of poly (lactic-co-glycolic acid) (PLGA). In vivo, carotid ligation injury was induced in mice to induce NH, with or without sulfasalazine containing nanoparticles (NP-SSZ) treatment. After four weeks, the arteries were collected for histology, immunofluorescence, Western blotting (WB) and qRT-PCR. In vitro, VSMCs were treated with TNF-α to induce cell proliferation and migration, followed by SSZ or vehicle treatment. WB was performed to further explore its mechanism. Results: The ratio of intima to media thickness (I/M) was increased after ligation injury on day 28, while the ratio was significantly reduced in the NP-SSZ treatment group. The dual positive nuclei of Ki-67 and α-SMA were 47.83±9.15%, whereas only 29.83±5.98% in the NP-SSZ-treated group (P<0.05). Both MMP-2 and MMP-9 were decreased in the NP-SSZ treatment group (P<0.05, P<0.05, respectively) compared to the control group. The levels of the targeted inflammatory genes (TNF-α, VCAM-1, ICAM-1, MCP-1) were lower in the NP-SSZ treatment group compared with the control group. In vitro, the proliferating cell nuclear antigen (PCNA) expression was significantly decreased in the SSZ treatment group. The cell viability of VSMCs was markedly increased in the TNF-α treatment group, whereas SSZ treatment inhibited this effect. LC3 II and P62 protein expression were higher in the NP-SSZ group than in the vehicle group both in vitro. The phosphorylation of NF-kB (p-NF-kB) and the phosphorylation of mTOR (p-mTOR) were decreased in the TNF-α+ SSZ group, whereas the P62 and LC3 II expression levels were increased. However, the expression level of p-mTOR, P62, and LC3 II was reversed after co-treatment with the agonist of mTOR MHY1485, whereas the p-NF-kB expression level was unchanged. Conclusion: SSZ inhibited VSMC proliferation and migration in vitro and NH in vivo through NF-kB/mTOR-mediated autophagy.